2015
DOI: 10.2217/imt.15.61
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-Induced Killer Cells as Immunotherapy for Solid Tumors: Current Evidence and Perspectives

Abstract: Cytokine-induced killer (CIK) cells are ex vivo expanded T lymphocytes endowed with potent MHC-independent antitumor activity. CIK cells are emerging as promising therapeutic approach in the field of cancer adoptive immunotherapy, with biologic features favoring their transferability into clinical applications. Aim of this review is to present the biologic characteristic of CIK cells, discussing the main preclinical findings and initial clinical applications in the field of solid tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 97 publications
0
24
0
Order By: Relevance
“…Clinical studies with CAR T cell strategies, showed that T cells exhibit the capability to home to tumor sites, as well as to proliferate, persist, and release cytokines upon encountering tumors. In comparison, these capabilities were minimal among WT CIK cells showing limited anti-tumor activity in preclinical analysis [ 50 - 53 ]. However, CAR engineering may comprise synergism or even additive effects of CAR- and NKG2D-mediated killing provided by CIK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies with CAR T cell strategies, showed that T cells exhibit the capability to home to tumor sites, as well as to proliferate, persist, and release cytokines upon encountering tumors. In comparison, these capabilities were minimal among WT CIK cells showing limited anti-tumor activity in preclinical analysis [ 50 - 53 ]. However, CAR engineering may comprise synergism or even additive effects of CAR- and NKG2D-mediated killing provided by CIK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Early evidence from clinical trials support the feasibility and safety profile of CIK immunotherapy, with initial signs of activity and positive impact on survival outcomes in multiple solid tumors, including ovarian cancer either in advanced 31,34,38,42,[59][60][61] or even adjuvant or post-chemotherapy maintenance settings 62 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to differentiation therapeutic strategy, HLA-I-independent tumor cell killing by cytokine-induced killer cell may be another promising method to target these HLA-I(−) cells (Giraudo et al , 2015). Our future efforts are focused on the characterization of the similarities and differences of the HLA-I enriched population in other sarcomas, given the breadth of biologies they represent, as well as the mechanisms at hand in the parallel differentiation and loss of neoplastic potential of HLA-I(−) cells in different cancer subtypes.…”
Section: Discussionmentioning
confidence: 99%